2018
DOI: 10.1007/s11099-018-0830-8
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen peroxide in regulation of plant metabolism: Signalling and its effect under abiotic stress

Abstract: In plants, hydrogen peroxide (H 2 O 2) acts as a signalling molecule that facilitates various biochemical and physiological processes. H 2 O 2 is a versatile molecule, involved in several cellular processes both under stress and stress-free conditions. In regulating plant metabolism under stress conditions, exogenous application of H 2 O 2 also plays a pivotal role which is manifested in improved growth, photosynthetic capacity, and antioxidant protection. Abiotic stress is an inevitable environmental factor t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(41 citation statements)
references
References 152 publications
(131 reference statements)
3
38
0
Order By: Relevance
“…Hydrogen peroxide is safe and can be easily detoxified by an antioxidative enzyme system; catalase, peroxidase, ascorbate peroxidases. It is well reported that H 2 O 2 plays a signaling role in plants under stress and pathogen defense [36][37][38] -especially against virus infection, as reported by Mejía-Teniente and Durán-Flores et al [18]. In this work, treatment with H 2 O 2 improves the growth of watermelon plants and protects against CGMMV infection.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Hydrogen peroxide is safe and can be easily detoxified by an antioxidative enzyme system; catalase, peroxidase, ascorbate peroxidases. It is well reported that H 2 O 2 plays a signaling role in plants under stress and pathogen defense [36][37][38] -especially against virus infection, as reported by Mejía-Teniente and Durán-Flores et al [18]. In this work, treatment with H 2 O 2 improves the growth of watermelon plants and protects against CGMMV infection.…”
Section: Discussionsupporting
confidence: 64%
“…Treatment with H 2 O 2 ±infection was able to increase amounts of chl a, chl b and carotenoids of leaves significantly. The increase was concomitant with the concentration of H 2 O 2 [36], treatments with which increased PSII photochemical efficiency. Moreover, H 2 O 2 treatments increased the activity of Rubisco.…”
Section: Discussionmentioning
confidence: 90%
“…H 2 O 2 is relatively stable in vivo compared to other ROS molecules [44]. It is established that H 2 O 2 acts as a signaling molecules with tremendous impact on plant growth and development [24]. Production of ROS is a hallmark of successful recognition of infection and activation of plant defenses.…”
Section: Discussionmentioning
confidence: 99%
“…In a stress situation, e.g., in pathogen attack, plants develop several different defense strategies mediated by ROS [23,24]. ROS play two roles during plant-pathogen interactions.…”
Section: Introductionmentioning
confidence: 99%
“…It has been considered as an important signalling molecule that mediates various physiological and biochemical processes in plants. The role of H 2 O 2 in plant biochemistry and physiology has been widely described in literature (Apel and Hirt, 2004;Hung et al, 2005;Slesak et al, 2007;Khan et al, 2018). Recent studies have demonstrated that H 2 O 2 is a key signalling molecule in several biochemical pathways associated with abiotic stress response.…”
Section: Introductionmentioning
confidence: 99%